Ward pharmacy: a foundation for prescribing audit?. Issue 1 (March 1992) - Batty, R; Barber, N
Abstract : OBJECTIVES–To determine the extent and nature of prescription monitoring incidents by hospital pharmacists and to derive a performance indicator to allow prescription monitoring to be compared among hospitals in North West Thames region. DESIGN–Survey of all self recorded prescription monitoring incidents for one week in June 1990. SETTING–All (31) acute hospitals in the region with pharmacy departments on site, covering 10, 337 beds. SUBJECTS–210 pharmacists. MAIN MEASURES–Number of prescription monitoring incidents recorded, their nature, and outcome; a performance indicator of prescription monitoring (incidents/100 beds/week) and its variation according to specialty and site. RESULTS–3273 prescription monitoring incidents were recorded (median 89 per hospital, range 3-301), the most common being related to the dose and frequency of administration of the drug (933 incidents, 29%). These incidents led to alterations of prescriptions on 1611 occasions; the pharmacist's advice was rejected on 81. The greatest number of prescription monitoring incidents/100 beds/week by specialty was recorded for intensive therapy units (median 75); the medians for medicine and surgery were 32 and 21 respectively. This performance indicator varied 20-fold when analysed by site, values ranging from 3.6 to 82.1 (median 29.8). CONCLUSIONS–Hospital pharmacists play a large part in monitoring and improving prescribing, and most of their interventions are related to the basics of prescribing. They therefore have a role in medical audit, working with clinicians to identify prescribing problems, and to set standards and monitor practice. A performance indicator of prescription monitoring incidents/100 beds/week allows comparison of pharmacists' activities among sites and may be a valuable tool in auditing them.